Comparison of tricuspid and mitral annular plane systolic excursion in determination of acute blood loss in healthy volunteers - Sarıhan, Aydın; Güllüpınar, Birdal; Sağlam, Caner; Karagöz, Arif; Tandon, Shikha; Turhan, Ajda; Koran, Serhat; Ünlüer, Erden Erol (Springer Science and Business Media Deutschland GmbH, 2023)
Ultrasound is used more and more in determining acute blood loss. This study is to compare tricuspid annular plane systolic excursion (TAPSE) and mitral annular plane systolic excursion (MAPSE) measurement to determine volume loss pre and post blood donation in healthy volunteers. The systolic, diastolic and mean arterial blood pressures and pulses of the donors were measured in the standing and supine position by the attending physician, then, inferior vena cava (IVC), TAPSE and MAPSE measurements were made pre and post blood donation. Statistically significant differences were found in systolic blood pressure and pulse rate values that obtained in the standing position, and in the systolic blood pressure, diastolic blood pressure, mean arterial pressure and pulse values that obtained in the supine position (p < 0.05). The difference between IVC expiration (IVCexp) pre and post blood donation was 4.76 +/- 2.94 mm, and the difference in IVC inspiration (IVCins) was 2.73 +/- 2.91 mm. In addition, the MAPSE and TAPSE differences were 2.16 +/- 1.4 mm and 2.98 +/- 2.13 mm, respectively. Statistically significant differences were found between IVCins-exp, TAPSE and MAPSE values. TAPSE and MAPSE can be helpful in the early diagnosis of acute blood loss.
Keywords: Acute Blood Loss; Early Diagnosis; Mitral Annular Plane Systolic Excursion; Tricuspid Annular Plane Systolic Excursion